Developing a set of consensus indicators to support maternity service quality improvement: Using Core Outcome Set methodology including a Delphi process - Bunch, K; Allin, B; Jolly, M; Hardie, T; Knight, M (Wiley, 2018)
Objective: To develop a core metric set to monitor the quality of maternity care Design: Delphi process followed by a face-to-face consensus meeting Setting: English Maternity units Population: Three representative expert panels: service designers, providers and users Main Outcome Measures: Maternity care metrics judged important by participants Methods: Participants were asked to complete a two phase Delphi process, scoring metrics from existing local maternity dashboards. A consensus meeting discussed the results and re-scored the metrics Results: 125 distinct metrics across six domains were identified from existing dashboards. Following the consensus meeting, 14 metrics met the inclusion criteria for the final core set: • Smoking rate at booking • Rate of birth without intervention • Caesarean section delivery rate in Robson group 1 women • Caesarean section delivery rate in Robson group 2 women • Caesarean section delivery rate in Robson group 5 women • 3rd and 4th degree tear rate among women delivering vaginally • Rate of postpartum haemorrhage of 1500ml or greater • Rate of successful vaginal birth after a single previous caesarean section • Smoking rate at delivery • Proportion of babies born at term with an Apgar score <7 at 5 minutes • Proportion of babies born at term admitted to the neonatal intensive care unit • Proportion of babies readmitted to hospital at <30 days of age • Breastfeeding initiation rate • Breastfeeding rate at 6-8 weeks Conclusions: Core outcome set methodology can be used to incorporate the views of key stakeholders in developing a core metric set to monitor the quality of care in maternity units thus enabling improvement